Pengaruh Media Scrapbook Terhadap Kemampuan Berpikir Kreatif - Arif Rahman Hakim; . Nurrahmah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Bima, 2021)
This study aims to determine the effect of scrapbook media on students' creative thinking skills. The type of research used is Quasi Experiment using the Nonequivalent Control Group Design research design with a sample of fifth grade students at SDN 59 Rasalewi, Bima City. The instruments used in this research are test instruments and observation sheets. Analysis of the data used in the form of percentage analysis for students' creative thinking skills, N-gain test and t-test. The results of data analysis show that from 21 students the total number of students is 76.19% or 16 students get the N-gain in the very high category and 23.81% or 5 students get the influence in the high category. The t-test results show that tcount = 2.259 > ttable = 1.725 (significant level = 0.05) so Ha is accepted and H0 is rejected. Thus, it can be concluded that there is a significant effect of using scrapbook media on students' creative thinking abilities.